2021
DOI: 10.1371/journal.pone.0255968
|View full text |Cite
|
Sign up to set email alerts
|

Development of mammary cancer in γ-irradiated F1 hybrids of susceptible Sprague-Dawley and resistant Copenhagen rats, with copy-number losses that pinpoint potential tumor suppressors

Abstract: Copenhagen rats are highly resistant to mammary carcinogenesis, even after treatment with chemical carcinogens and hormones; most studies indicate that this is a dominant genetic trait. To test whether this trait is also dominant after radiation exposure, we characterized the susceptibility of irradiated Copenhagen rats to mammary carcinogenesis, as well as its inheritance, and identified tumor-suppressor genes that, when inactivated or mutated, may contribute to carcinogenesis. To this end, mammary cancer–sus… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 41 publications
0
1
0
Order By: Relevance
“…Termination occurred at 90 weeks of age [ 18 , 20 , 22 ], 100 weeks of age [ 21 ] or was not set (i.e. the rats died naturally or were sacrificed only upon general deterioration) [ 19 ]; in a subset of studies, the rats with one or more palpable tumors were autopsied at 50 weeks of age, and those without palpable tumors at that time were checked until a tumor(s) could be palpated, at which time autopsy was done [ 14–17 ]. Acute whole-body irradiation with 137 Cs γ rays (0.5–0.6 Gy/min) was performed once at either 1, 3, 7, 13 or 15 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…Termination occurred at 90 weeks of age [ 18 , 20 , 22 ], 100 weeks of age [ 21 ] or was not set (i.e. the rats died naturally or were sacrificed only upon general deterioration) [ 19 ]; in a subset of studies, the rats with one or more palpable tumors were autopsied at 50 weeks of age, and those without palpable tumors at that time were checked until a tumor(s) could be palpated, at which time autopsy was done [ 14–17 ]. Acute whole-body irradiation with 137 Cs γ rays (0.5–0.6 Gy/min) was performed once at either 1, 3, 7, 13 or 15 weeks of age.…”
Section: Methodsmentioning
confidence: 99%
“…Regardless of the radiological agent and administration mode, irradiated rats appear to undergo a similar somatic mutational reaction to the radiation, leading to the development of corresponding mammary tumor identities [ 239 , 242 ]. Such tumors have been shown to develop within approximately 140 days to up to one year succeeding radiation exposure, with neoplasm incidence being directly proportional to the dose given [ 137 , 243 ].…”
Section: Introductionmentioning
confidence: 99%
“…Among the different rat models used to study radiation-induced carcinogenic effects, previous studies have demonstrated tumorigenesis susceptibility in at least 4 different strains, namely the Sprague-Dawley (SD), Wistar-related, including Wistar Albino Glaxo and Lewis, Copenhagen, and Long-Evans (LE) rats [ 231 , 233 , 235 , 243 , 245 , 246 ]. In particular, SD rats demonstrate elevated sensitivity to radiation, also at low doses, linked to a high incidence of mammary neoplasms [ 245 , 247 ].…”
Section: Introductionmentioning
confidence: 99%